﻿Revision of the genus Urvaschia Hopp (Hemiptera, Lygaeoidea, Oxycarenidae), with descriptions of two new species from China and Nepal - Cuiqing Gao; Shiya Xiao; Előd Kondorosy (ZooKeys, 2022)
The species of Urvaschia Hopp, 1987 are reviewed. The following taxonomic change is proposed: Urvaschia obscuripennis (Kiritshenko, 1914), comb. nov. (transferred from Microplax Fieber, 1860). The genus Urvaschia Hopp is newly recorded from Afghanistan, China, Iran, and Tadzhikistan. Two new species of Urvaschia, Urvaschia convexa sp. nov. and U. recta sp. nov. are described from China and Nepal. A diagnosis of the genus, a key to all of the included species, habitus photographs, and male genitalia illustrations of selected species are presented.